2021
DOI: 10.1016/j.ajog.2021.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Services and payer mix of Black-serving hospitals and related severe maternal morbidity

Abstract: BACKGROUND: Black-serving hospitals are associated with increased maternal risk. However, prior administrative data research on maternal disparities has generally included limited hospital factors. More detailed evaluation of hospital factors related to obstetric outcomes may be important in understanding disparities. OBJECTIVE: To examine detailed characteristics of Black-serving hospitals and how these characteristics are associated with risk for severe maternal morbidity (SMM). METHODS: This serial cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…In addition, payer mix with greater proportions of Medicaid-covered or uninsured patients, as would be seen in areas where patients with private insurance bypass nearest hospitals, is associated with L&D unit closures, inability to cover costs of services such as obstetric analgesics and higher maternal mortality. [19][20][21] Like our results, bypassing behavior in obstetrics and other areas of health care is most frequently observed in White, high socioeconomic status patients. 4,12,13,15 Existing literature suggests that perception of care quality and service availability are key factors in parental choice of birthing facility.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, payer mix with greater proportions of Medicaid-covered or uninsured patients, as would be seen in areas where patients with private insurance bypass nearest hospitals, is associated with L&D unit closures, inability to cover costs of services such as obstetric analgesics and higher maternal mortality. [19][20][21] Like our results, bypassing behavior in obstetrics and other areas of health care is most frequently observed in White, high socioeconomic status patients. 4,12,13,15 Existing literature suggests that perception of care quality and service availability are key factors in parental choice of birthing facility.…”
Section: Introductionsupporting
confidence: 78%
“…Many small‐town, micropolitan areas are served by a single L&D unit and the increase in parental choice to bypass these facilities from 2013 to 2019 in favor of those located in large, metropolitan areas could be an indication of future cessation of services. In addition, payer mix with greater proportions of Medicaid‐covered or uninsured patients, as would be seen in areas where patients with private insurance bypass nearest hospitals, is associated with L&D unit closures, inability to cover costs of services such as obstetric analgesics and higher maternal mortality 19–21 …”
Section: Bypass Do Not Bypass Total Risk Ratiomentioning
confidence: 99%
“…We included hospital payer information from hospital discharge records (private insurance, public insurance, other/uninsured/unknown) as a covariate in our models as a potential risk factor that may indicate where individuals reside, the availability of socioeconomic opportunities, hospital resources, as well as SMM risk 40 …”
Section: Methodsmentioning
confidence: 99%
“…Analysis of 2007–2012 California data examining birth hospitals and excess SMM showed that birth hospital accounted for only 7.8% of the Black-White SMM disparity and between 16.1 and 24.2% for all other racial and ethnic group disparities [22 ▪▪ ]. Study of 2010–2011 NIS and the 2013 American Hospital Association Annual Survey Databases showed that the lowest Black-serving hospital quartile carried the lowest SMM risk and exploration of Black-serving hospital characteristics showed that they were more likely to have Medicaid insurance payers and specialized medical, pediatric, surgical, and safety-net services [23 ▪▪ ]. New York City Hospital data from 2010 to 2014 showed that Black and Hispanic women birth at hospitals with worse outcomes for both women and very preterm infants.…”
Section: Risk Indicators For Obstetrical Disparitiesmentioning
confidence: 99%